Situation Report: Czechoslovakia, 20 January 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Czechoslovak Economy in 1989 / by Peter Martin New Charter 77 Spokesmen / by Jiri Pehe Vaclav Havel Issues an Appeal against the Planned Suicide of a Student / by Jiri Pehe The Authorities Suppress the Commemoration of Jan Palach's Death / by Jiri Pehe The Problems of Computerization / by Jan Obrman The Teaching of History Criticized / by Jan Obrman Who Issued the Ban on Many Czech Writers in the 1960s? / by Jiri Pehe Can Czechoslovak Monuments Be Saved? / by Antonin Kratochvil